2007
DOI: 10.1080/01485010600915152
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Sperm Extraction and ICSI in Patients with Post-Chemotherapy Non-Obstructive Azoospermia

Abstract: Japan146 MD-TESE procedures were performed in 74 patients presenting with non-obstructive azoospermia (NOA). Five of the 74 patients displayed a history of chemotherapy. Etiology of chemotherapies included testicular cancer, osteosarcoma, Ewing sarcoma, and malignant lymphoma of the stomach. Post-chemotherapy duration was 2.5-18 years. All patients underwent MD-TESE using local anesthesia with spermatic block and sedation. Extracted sperm was cryopreserved for ICSI. Histopathologic examination revealed Sertoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…In our study, we have shown that half of the men (50.7%) unable to cryopreserve sperm prior to cancer treatment and diagnosed with permanent azoospermia had successful sperm retrieved with TESE and usable for at least one ICSI cycle, a rate similar to the control group. Our data is in line with the results of previous reports (from a total of 258 patients and 283 surgical retrievals, the rate of sperm recovery was 45.9%) [36][37][38][39][40][41][42][43] and also confirm that not all forms of cancer benefit from successful sperm recovery [39].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, we have shown that half of the men (50.7%) unable to cryopreserve sperm prior to cancer treatment and diagnosed with permanent azoospermia had successful sperm retrieved with TESE and usable for at least one ICSI cycle, a rate similar to the control group. Our data is in line with the results of previous reports (from a total of 258 patients and 283 surgical retrievals, the rate of sperm recovery was 45.9%) [36][37][38][39][40][41][42][43] and also confirm that not all forms of cancer benefit from successful sperm recovery [39].…”
Section: Discussionsupporting
confidence: 92%
“…Cumulative live birth rates per couple in NOA cancer survivors did not differ from non-cancer NOA patients (40 vs. 46.5%), despite the significantly older age of the female partners in cancer survivors. However, compared with data in literature (60 deliveries out of 122 couples = 49.2%) [36][37][38][39][40][41][42][43], we showed a lower live birth rate, and this might reflect the mean older age of the female partners in our dataset [44]. The rate of first trimester (< 12 weeks) miscarriage were higher in both NOA and RE/FOE cancer survivors, than in the non-oncologic controls.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Eleven retrospective studies 26 29 30 31 32 33 34 35 36 37 38 and 8 case reports or case series 39 40 41 42 43 44 45 46 reported results for postgonadotoxic treatment TESE. The case reports and case series mainly reported TESEs that allowed for spermatozoa retrieval, while the retrospective studies reported between 33.3% and 76.2% positive TESEs ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies on testicular stem cell transplantation are not available as yet. If no sperm was frozen before treatment, testicular sperm extraction (TESE) followed by ICSI can still offer a chance at fatherhood for patients with post-chemotherapy azoospermia [37,38].…”
Section: Semen Cryopreservationmentioning
confidence: 99%